3D Shape Deformation Using Stick Figures. (October 2022) - Seylan, Çağlar; Sahillioğlu, Yusuf
Abstract: Obtaining new poses of an articulated character is a critical task in computer graphics. We address this issue with a new shape deformation approach consisting of two phases enabling the user to express the new pose as a simple stick figure, also called skeleton consisting of few bones. We interchangeably refer to this problem as shape transfer because the template shape is transferred to the independent stick figure that may be obtained from any source such as motion capture and 3D sketching. In the first phase, the stick figure is embedded into the template shape, resembling the rigging process of character skinning. Then, instead of computing blend weights as in skinning, the shape, discretized as a mesh, is augmented by adding extra edges between a subset of mesh vertices and the embedded stick figure. The second phase deforms the augmented mesh towards the new pose under the guidance of the embedded stick figure by minimizing an As-Rigid-As-Possible (ARAP) energy. The overall deformation is intuitive as skinning, preserves surface details as it is based on ARAP deformation yet has better volume preservation capability owing to the augmented mesh. Our results are validated both in terms of timing and accuracy in a comprehensive test suite that includes state-of-the-art deformation techniques. Highlights: Edges between mesh and its skeleton prevent from volume loss in ARAP deformation. Two skeletons can be matched by minimizing a distance-based penalty function. Distance-based skeleton matching method can be used as an automatic rigging method. New poses of a shape can be created by using a stick figure and a template mesh.